Doing palliative care research on hematologic cancer patients: A realist synthesis of literature and experts’ opinion on what works, for whom and in what circumstances - Tanzi, Silvia; Martucci, Gianfranco (Frontiers in Oncology, 2023)
Background: Research in PC is frequently challenging for patient’s frailty, study design, professional misconceptions, and so on. Little is known about specificity in PC research on Hematologic cancer patients, who have distinct characteristics that might influence the enrollment process. Aims: What works, how and for whom, in increasing enrollment in studies in hematologic PC? Methods: Realist review: a qualitative review whose goal is to identify and explain the interaction between contexts, mechanisms, and outcomes (CMOs). The theory was informed by a narrative, theory-based literature research, including a starting systematic research, and the addition of papers suggested by experts of the field. We also used 7 interviews with experts in hematologic PC research and our own experience from a PC hematological pilot study to refine the initial theory. Results: In our initial theory we hypothesize that: - access to palliative care could be beneficial to hematologic patients, even in early stages - hematologists tend to under-use palliative care services in general, due to unpredictable disease trajectories and cultural barriers. - these factors may negatively impact the patients’ enrollment in PC research We included secondary literature as narrative reviews, if they presented interesting propositions useful for our theoretical construction. 23 papers met our inclusion criteria. We also searched for relevant CMOs impacting referral in palliative care, and we selected a list of CMOs that could be relevant also in hematology. We accordingly theorized a group of interventions that could increase the enrollment in PC research and presented them using “social exchange theory” (SET) as a theoretical framework. Prominent researchers in hematologic PC were interviewed on their opinion on our results, and additional CMOs. Conclusions: Before conducting research in PC on hematologic patients, it’s probably advisable to assess: - the perception of the different actors, in particular the hematologists, in terms of pros and cons of referral to PC and enrollment in PC trials - the existing relationship between PC and the Hematology department Accordingly, it’s possible to tailor different interventions on the various actors and choose a model of trial to increase of the perception of benefits from PC and, consequently, enrollment.